The humanitarian impacts on internal conflicts in Indonesia: a national security analysis / Denik Iswardani and Sharifah Shahirah Syed Sheikh - Iswardani, Denik; Syed Sheikh, Sharifah Shahirah (CMIWS and UiTM Press, 2014)
Internal conflicts which frequently occur in some parts of Indonesia such as Aceh, Maluku, Poso and Papua have caused many casualties and losses. If it continues, this situation will threaten the regional security. This article explains the impact of the humanitarian problems as a result of internal conflicts in Indonesia by analysing the national security concept. By using secondary data obtained from literature review and observations in conflict areas, this study depicts that the internal conflicts that occur has led to insecurity of society, which could threaten for nation’s stability.